A new environment-friendly polyferric sulfate-catalyzed ozonation process for sludge conditioning to achieve deep dewatering and simultaneous detoxification. (20th July 2022) - Ge, Dongdong; Huang, Shouqiang; Cheng, Jiehong; Han, Ying; Wang, Yuhui; Dong, Yanting; Hu, Jinwen; Li, Guobiao; Yuan, Haiping; Zhu, Nanwen
Abstract: The dewaterability of sludge from biological sewage treatment plants is extremely poor since the highly hydrophilic biomacromolecules. This work developed a new polyferric sulfate-catalyzed ozonation (PFS/O3 ) process to disintegrate sludge flocks and extracellular hydrophilic substrates for liberating bound water. With 40 mg/gTS PFS catalyzing 60 mg/gTS O3, bound water content declined to 1.42 g/gTS, and water content of dewatered sludge dropped to 59.79%. Meanwhile, microbial cells were inactivated by 47.3%, and extracellular protein-like components were degraded substantially, rendering the neutral potential and low apparent viscosity. PFS/O3 treatment significant facilitated CHO-compound decomposition, reactions of nitrogenous groups, and P-containing biomolecule release. And more hydrophobic groups were exposed on the bio-matrix surface. Besides, polyhydroxy Fe as skeleton builder reconstructed sludge drainage passages for more water permeation. The predominant mechanism for enhancing sludge dewaterability in PFS/O3 process was the oxidation role of improved OH, and the chemical reaction chains were proposed tentatively. Moreover, this process simultaneously removed 26.95%–60.05% heavy metals and 31.18%–80.91% polycyclic aromatic hydrocarbons in dewatered sludge, and its chemical cost was preliminarily estimated as 88.80 USD/tonTS. Therefore, the PFS/O3 process was of great prospect and practical value in sludge treatment for dewatering and detoxification. Graphical abstract: Image 1 Highlights: A new PFS-catalyzed O3 process assisted sludge deep dewatering and detoxification. EPS conformation turned to be loosened with more hydrophobic groups exposed. Molecular composition and transformation of DOM were shown by ESI FT-ICR MS. Chemical reaction mechanism of PFS-catalyzed O3 was put forward for the first time. Polyhydroxy Fe serving as supporting skeleton rebuilt multihole drainage passages.